Human Resource Management Program Development Project: Strategy for Developing Vocational High School Teacher Competence through Learning Communities - Ely Jayaningrum; Ainur Rifqi; Nuphanudin; Syunu Trihantoyo (Postgraduate, University of Mataram, 2026)
The gap between national human resource development policies and teacher professional development practices in vocational schools is the main background of this research. This study aims to develop the